Diagnosis of Tuberculosis infection in HIV: A Review - Wahyudi, Hendra (CoinReads Media Prima, 2023)
The high prevalence and increasing incidence of HIV has adversely affected the control of several endemic diseases, including tuberculosis (TB). In HIV there is a progressive decrease in CD4 T cells which is associated with progressive damage to immunity, in the form of a severe decrease in digestive tract lymphoid cells, erythrocyte apoptosis, increased permeability of the digestive tract and finally massive CD4 T cell destruction. HIV will attempt to enter target cells (dendrite cells, macrophage cells), which are cells capable of expressing CD4 T cell receptors and express chemokine coreceptors (CCR5 or CXCR4) on the surface of CD4 T cells. HIV utilises CXCR4 to destroy CD4 T cells at acute onset, resulting in a decrease in CD4 T cell numbers. The condition of decreased CD4 T cell count in HIV will also be aggravated by the presence of TB co-infection. CD4 T cells contribute to controlling Mycobacterium tuberculosis. The adaptation of Mycobacterium tuberculosis in HIV patients can also weaken the cytokine immunity of interfor-γ, interleukin-10 patients in HIV infection. HIV-1 induces a decrease in CD4+ levels and the development of active tuberculosis. This review summarizes that Mycobacterium tuberculosis has an important component, Lipoarabinomannan (LAM), which has a broad ability to inhibit the influence of immunoregulators, thereby suppressing the proliferation of T lymphocytes, inhibiting macrophage activation and neutralising the influence of free radicals. Decreased immune status and nutritional status due to Mycobacterium tuberculosis can accelerate the course of HIV infection towards AIDS.